Tracking SDG 7 : The Energy Progress Report 2021 - International Energy Agency; International Renewable Energy Agency; United Nations Statistics Division; World Bank; World Health Organization (World Bank, Washington, DC, 2022)
The 2021 edition of Tracking SDG 7: The Energy Progress Report monitors and assesses achievements in the global quest for universal access to afordable, reliable, sustainable, and modern energy by 2030. The latest available data and selected energy scenarios reveal that at today’s rate of progress, the world is not on track to achieving SDG 7. This is particularly true of the most vulnerable countries and those that were already lagging. This report also examines various ways to bridge the gaps, chief among them the goal of significantly scaling up renewable energy while maximizing its socioeconomic benefits. While renewable energy has demonstrated remarkable resilience during the pandemic, the unfortunate fact is that gains in energy access throughout Africa are being reversed: the number of people lacking access to electricity is set to increase in 2020, making basic electricity services unaffordable for up to 30 million people who had previously enjoyed access. The COVID-19 crisis has revealed the stark worldwide inequalities in access to reliable energy and health care, especially in rural and peri-urban areas, and has highlighted the need to expand energy access to help populations mitigate the effects of the crisis. o!ers a snapshot of the primary indicators.